PURA DEWATA AGUNG IN SUMBERARUM VILLAGE, SONGGON DISTRICT, BANYUWANGI (STUDY OF THE HISTORY, STRUCTURE AND FUNCTIONS OF TEMPLES) - Andreyan Priyo Prayogo; I Kadek Yudiana; I Wayan Mertha; Mahfud (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This research was conducted in Sumberarum Village, Songgon, Banyuwangi which aims to find out (1) the history of the Dewata Agung Temple; (2) The structure of the Dewata Agung Temple; (3) The function of the Great Gods Temple. This research is historical research, so the steps taken are (1) Heuristic data collection (observation, interviews, study of documents), (2) Criticism of sources, (3) Interpretation and (4) Historiography of historical writing. Based on findings in the field, Pura Dewata Agung has existed since 1970 and before the establishment of Pura Dewata Agung, its name was Sanggar Pamujan, where this pamujan studio was used as a prayer for Jawi Wishnu Buddhists. Then in 1970, Jawi Wishnu Buddhists moved to Hindu Dharma because they had to choose one of the religions that have been determined and have legality in the new order government, then Buddha Jawi Wishnu inevitably has to change religions, one of which is to choose Buddhism or Hindu Dharma. This was then followed by Jawi Wishnu Buddhists deliberating with several Jawi Wishnu Buddhist leaders to find common ground to choose between Buddhism and Hindu Dharma. the result of the people's agreement that they chose Hindu Dharma because their considerations were based on the sacred texts of the Vedas and the same God who is worshiped, namely Sang Hyang Bhatara Wishnu. So that the Jawi Wishnu Buddhists in Sumberarum Village moved to Hindu Dharma and they worked together to start building the Great Gods Temple. The structure of the Dewata Agung Temple uses the Dwi Mandala concept in which this concept divides the temple into two parts, namely Nista Mandala (the unholy part) and Utama Mandala (the most sacred part). The function of the Great Gods Temple is divided into three namely, (1) Religious function as a place for prayer and religious ceremonies (2) Religious Education function as a place for pasraman or often called Hindu religious education; and (3) social function as a meeting place for meetings and deliberations. (1) Religious function as a place for prayer and religious ceremonies (2) Religious Education function as a place for pasraman or often called Hindu religious education; and (3) social function as a meeting place for meetings and deliberations. (1) Religious function as a place for prayer and religious ceremonies (2) Religious Education function as a place for pasraman or often called Hindu religious education; and (3) social function as a meeting place for meetings and deliberations.